The Effect of Students' Attitudes Towards Exercise, Diet and Body Composition on Students' Physical Fitness Post-Covid-19 - Rhama Mashuri; Kurnia Tahki; Yasep Setiakarnawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purposeof this study is to find out the direct influence of Exercise Attitude, Diet, and Body Composition on the Physical Fitness of students of Al- Azhar Islamic High School in Bekasi City as many as 62 samples using the Purposive Sampling withdrawal technique. data collection techniques in the form of numbers, written statements, as well as oral information and various facts based on the focus on the research being studied. By giving questionnaires / questionnaires with a likert scale. and Observation. The analysis technique uses a path analysis approach (path analysiss). The results of the analysis were obtained, as follows: 1). There is a significant influence of Exercise Attitudes on Physical Fitness. 2). There is a significant influence between Diet and Physical Fitness. 3) There is a significant influence between Body Composition on the Physical Fitness of Students of Al-Azhar Islamic Senior High School, Bekasi City in the Post-Covid-19 Period.